Types of precompetition anxiety among junior athletes - Popovych, I.; Sirko, R.; Dushka, A.; Slobodianyk, V.; Stelmakh, O.; Pylypenko, L.; Zahrai, L. (Journal of Physical Education and Sport, 2024)
The aim of the research is to categorize the types of pre-competition anxiety experienced by junior athletes immediately before official sports events. Methods: Valid and reliable psychodiagnostic tools, well-established in sports research, were utilized to accurately measure anxiety phenomena in junior athletes. Results: Descriptive frequency characteristics were analyzed to construct a comprehensive profile of pre-competition anxiety among the participants. K-means clustering identified four distinct types: "Destructive Anxiety Disorder" (DAD) (n = 42; 13.13%); "Personal Precompetition Anxiety" (PPA) (n = 120; 37.50%); "Situational Precompetition Anxiety" (SPA) (n = 102; 31.87%); and "Social Unprotected Anxiety" (SUA) (n = 56; 17.50%). Notably, DAD is the most concerning type, potentially impacting both performance and the athlete's overall health. Additionally, SUA was identified as posing significant risks, as this type can become a plateau of stagnation and later transform into a psychological problem. It was highlighted that anxiety plays an important role in an athlete`s sporting activities, and it is crucial for junior athletes to efficiently utilize their resources. We compared the types of pre-competition anxiety among junior athletes representing team sports (Group 1) and individual sports (Group 2) using Fisher`s criterion (f). Two statistically significant advantages were established: Group 1 (n = 79; 49.37%) has an advantage in "SPA" (f = 1.89; p = .05); Group 2 (n = 42; 26.25%) has an advantage in "SUA" (f = 2.12; p = .05). Discussion and conclusions: The types of junior athletes` pre-competition anxiety are considered psycho-physiological states related to awaiting a sports competition, accompanied by psycho-emotional stress. These require the development of athletes` self-regulation, stress resistance, and resilience, and depend on their individual psychological characteristics, experience, and mastery. We recommend that coaching staffs diagnose the types of pre-competition anxiety to make timely corrections to an athlete`s performance, which can significantly impact the results of sports competitions and help protect athletes against injuries.